Irrigation Canal Network Flow Analysis by a Hydraulic Model†. (5th April 2016) - Kim, Hae‐Do; Kim, Jin‐Taek; Nam, Won‐Ho; Kim, Sun‐Joo; Choi, Jin‐Yong; Koh, Bo‐Sung
Abstract: For agricultural water management to be successfully achieved, flow analysis of irrigation canal network flows is essential to determine the proper distribution of crop water requirements and to contribute to an optimized irrigation operation and water allocation. This study developed a hydraulic analysis model for irrigation canal flow by using the Storm Water Management Model (SWMM) module by adding the network modelling and paddy water balance model. This model was applied to a rice paddy field rehabilitation project area in the Daesan District located in the western part of South Korea. Results obtained from the calibrated simulation model were compared with the actual measurement data from water‐level gauges at the irrigation canals. The irrigation hydraulic analysis model for canal network flow indicates the significance of using irrigation management tools in improving the analysis for accurate irrigation scheduling based on its simulation results, such as flow travel time, water level and flow amount. Copyright © 2016 John Wiley & Sons, Ltd.